2021
DOI: 10.1021/acsomega.1c00445
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Screening of Effective Anti-Insomnia Fractions of Zhi-Zi-Hou-Po Decoction via Drosophila melanogaster and Network Pharmacology Analysis of the Underlying Pharmacodynamic Material and Mechanism

Abstract: Insomnia is an anabatic epidemiology, while the mechanism is extremely complicated; it remains one of the major scientific challenges in life sciences. Because of the advantage of having a similar genetic background and circadian rhythm as those of humans, the Drosophila melanogaster model organism is hugely popular in sleep-related drug screening studies. Seven-day-old virgin D. melanogaster was used to establish the sleep deprivation model by repeated light stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…( Ma et al, 2021 ). As a classic Chinese prescription, ZZHPD has been proven to have a good effect on depression-like symptoms with few side effects ( Sun et al, 2021 ). However, due to the complex components and multi-target nature of ZZHPD, the mechanism in treating insomnia is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…( Ma et al, 2021 ). As a classic Chinese prescription, ZZHPD has been proven to have a good effect on depression-like symptoms with few side effects ( Sun et al, 2021 ). However, due to the complex components and multi-target nature of ZZHPD, the mechanism in treating insomnia is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These issues pose a big challenge for the evaluation of the clinical efficacy of TCM and for understanding of the material basis and molecular mechanisms responsible for its therapeutic efficacy. Fortunately, network pharmacology has evolved from systems biology and multidirectional pharmacology, thus revolutionizing the practice of TCM by shifting the paradigm of "one drug, one target, one disease" towards the model of "multicomponent, multitarget, multidisease," therefore making it possible to uncover the complex relationship between active components and their targets Yu et al, 2018;Sun et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile the promotion of Bax, downregulation of Bcl-2, and increase of apoptosis rate were observed after insomnia. 10 Previous studies indicated that silencing of SIRT4 exacerbated the expression of pro-inflammatory cytokines such as IL-1β, IL-6, IL-8, cyclooxygenase-2 (COX2), matrix metalloproteinase-9 (MMP-9), and intercellular adhesion molecule-1 (ICAM-1). 15 The upregulation of these genes is related to inflammation and vascular remodeling.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…Continuous neuroinflammatory reaction can induce neuronal apoptosis and cause many central injuries. 10 Some neurobiological studies have shown that there is a correlation between neuronal apoptosis and insomnia. 11 Some antiinsomnia drugs present neuroprotective and antiapoptotic effects on neurons.…”
Section: Introductionmentioning
confidence: 99%